(untitled) (World Economics and Finance Bulletin, 2022)
The main purpose of this research is to shed a light on the debt financing of commercial banks in Iraq and find how Iraqi banks finance investments and the effect of debt financing on the investment decisions , by analyzing and estimating the debt financing indictors of the selected variables and statistically testing as well as the indicator for measuring the independent variable for debt financing in commercial banks which is (the percentage of total debt), while the dependent variable for the axis of the investment decision which is (the rate of return on investment) . the sample of this research consists of (3) Iraqi banks listed in the Iraqi Stock Exchange were selected on the basis of availability of information necessary for the period of (10) years from (2010-2019). the result of research approved is negative relationship between the debt financing and the rate of return on investment on side and other side there are many factors influence on the rate of return on investment: such as (financing Deposit, company growth, company size). While the research recommended the senior and executive departments of banks to work hard in order to form and manage investment portfolios in a professional and efficient manner in order to avoid useless investment projects and so that the bank does not bear unnecessary financial costs